2016
DOI: 10.1108/bij-05-2015-0049
|View full text |Cite
|
Sign up to set email alerts
|

Multicriteria model for selecting TQM consultancy and certification services

Abstract: Purpose The purpose of this paper is to establish the need and the importance of adopting a structured model to support the decisions by using a multicriteria focus to guide drawing up a methodological framework. In addition, this study considers the maturity level of the organization, and the importance of continuous improvement after implementing ISO 9001. Design/methodology/approach This study presents a scientific technical foundation of the qualifying and selection criteria of the consultancy and Accred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…An extensive investigation of literature in the field of TQM has revealed that, a lot of research have been conducted to identify possible TQM implementation barriers and their impact on operational (Aamer et al , 2017; Maistry et al , 2017; Teixeira et al , 2015), organizational (Baidoun et al , 2018; Aquilani et al , 2017; Calvo-Mora et al , 2014), financial (Baidoun et al , 2018; Aquilani et al , 2017; Teixeira et al , 2015; Calvo-Mora et al , 2014) and non-financial performance of a service or manufacturing organization. However, a number of barriers along with their supportive links with organizational performance are evident from previous literatures (Saleh et al , 2018; Patyal and Koilakuntla, 2018; Aquilani et al , 2017; Maistry et al , 2017; Tavares de Aquino and Maciel de Melo, 2016; Jaeger and Adair, 2016; Teixeira et al , 2015; Calvo-Mora et al , 2014). But, a few researches have been conducted on finding relative importance of TQM barriers (Aamer et al , 2017; Talib and Rahman, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…An extensive investigation of literature in the field of TQM has revealed that, a lot of research have been conducted to identify possible TQM implementation barriers and their impact on operational (Aamer et al , 2017; Maistry et al , 2017; Teixeira et al , 2015), organizational (Baidoun et al , 2018; Aquilani et al , 2017; Calvo-Mora et al , 2014), financial (Baidoun et al , 2018; Aquilani et al , 2017; Teixeira et al , 2015; Calvo-Mora et al , 2014) and non-financial performance of a service or manufacturing organization. However, a number of barriers along with their supportive links with organizational performance are evident from previous literatures (Saleh et al , 2018; Patyal and Koilakuntla, 2018; Aquilani et al , 2017; Maistry et al , 2017; Tavares de Aquino and Maciel de Melo, 2016; Jaeger and Adair, 2016; Teixeira et al , 2015; Calvo-Mora et al , 2014). But, a few researches have been conducted on finding relative importance of TQM barriers (Aamer et al , 2017; Talib and Rahman, 2015).…”
Section: Introductionmentioning
confidence: 96%